CAPAIAN PELAYANAN AIR BERSIH PERDESAAN SESUAI MILLENNIUM DEVELOPMENT GOALS – STUDI KASUS DI WILAYAH DAS BRANTAS - Ali Masduqi (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
The pipelined water supply services in rural areas of East Java Province in 2004 were 5.5%. This achievement must be improved to reach the Millennium Development Goals (MDGs) target. The target of the MDGs by 2015, is to reduce the proportion of people without sustainable access to safe water supply by 50%. In order to achieve the target, it is necessary to evaluate the constraints which may block the service achievement. This study was conducted in the Brantas River Basin, involving 360 rural water supply systems. Data obtained showed that the water services level in pipeline system in rural areas was only 8.60% in 2005. The achievement of services must be improved up to 40% in 2015, to meet the MDGs target. This target will be achieved if the construction of water supply facilities consider the constraints of poverty and lack of participations. If two constraints above are not controlled, the water supply services achievement will be only 26.2% in 2015.